Development of a Predictive Model for Suicidal Tendency in Individuals with Borderline Personality Disorder Based on Thwarted Belongingness, Perceived Burdensomeness, and Acquired Capability for Suicide: Testing Joiner's Model - Khandaghi Khameneh, Zahra; Zargham Hajebi, Majid; Jalali, Mohammad Reza (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: The aim of the present study was to predict suicidal tendency in individuals with borderline personality disorder based on thwarted belongingness, perceived burdensomeness, and acquired capability for suicide, as per the Joiner model.Methods and Materials: The research method was correlational, utilizing structural equation modeling (SEM) to analyze the structural relationships. The study population comprised all male and female adults aged 18 to 40 years who visited psychiatric wards and clinics in Tehran during 2021, were diagnosed with borderline personality disorder, and had a history of suicide attempts, suicidal tendency, or suicidal thoughts as determined by screening questions. The sampling was done purposefully through patient screening. According to Kline's theory for SEM designs, the sample size was 500 participants. Suicidal tendency was assessed using the Beck Scale for Suicide Tendency (BSSI), acquired capability for suicide was measured using the Suicide Behaviors Questionnaire-Revised (SBQ-R), and perceived burdensomeness was assessed using the Interpersonal Needs Questionnaire (INQ). Data analysis was performed in SPSS and AMOS using SEM.Findings: The results of the structural equation analysis indicated that the proposed research model had an acceptable fit, and the model predicting suicidal tendency in individuals with borderline personality disorder through thwarted belongingness, perceived burdensomeness, and acquired capability for suicide, as per Joiner's model, was confirmed. Additionally, the secondary results showed that among these variables, acquired capability for suicide played the most significant role in suicidal tendency in individuals with borderline personality disorder. The direct effect of thwarted belongingness, or the experience of alienation from others, on suicidal tendency was approximately 0.23, the effect of perceived burdensomeness was approximately 0.26, and the effect of acquired capability for suicide on suicidal tendency in individuals with borderline personality disorder was approximately 0.28. Consequently, a total of 0.78% of the variance in suicidal tendency in affected individuals can be explained by these three variables, which are the variables of Joiner's model.Conclusion: Thus, the interpersonal theory of suicide proposed by Joiner was confirmed in individuals with borderline personality disorder who participated in this study.